Evaluation of Bureaucratic Reforms in Realizing World Class Government in Tuban - Iswanto, Denny; Putra, Ringga Ananta (Universitas Sebelas Maret, 2023)
The purpose of this study is to evaluate the performance of bureaucratic reform in making changes to the system of government administration in the aspects of institutional (organization), management (business process), and human resources of the apparatus. Various studies show that local government bureaucratic reform tends to be slow due to various obstacles experienced, one of which is in Tuban Regency. Bureaucratic reform in the Tuban Regency Government is implemented based on eight areas of change to improve the quality of public services. However, there are still many obstacles faced, including the quality of apparatus resources, low accountability, and inadequate electronic-based government capabilities. This research method uses a qualitative method with a document study approach and uses secondary data analysis techniques, namely researchers using materials sourced from books, agency reports, and the internet to obtain data from relevant sources. The results showed that the bureaucratic reform in Tuban district has carried out performance evaluations based on the assessment of each program's achievement. In the aspect of building a clean and accountable bureaucracy, the SAKIP index is still low and experiencing a decline and the Anti-Corruption Behavior Index is low and still below the national average. The aspect of bureaucratic capability is assessed based on the SPBE index which is only 50% running and the ASN professionalism index is still in the low classification. Third, the aspect of excellent service is seen from the low public service index, which shows that there is still a gap between service recipients and the reality of services provided to the community. There needs to be a holistic improvement in bureaucratic reform efforts to realize a world-class government that is clean and accountable, a capable bureaucracy, and a bureaucracy that can provide excellent service.